The rough guide to Bulgaria - Bousfield, Jonathan (Rough Guides, 2008)
A comprehensive guide to visiting Bulgaria that provides information on accommodations, restaurants, festivals, outdoor activities, the media, and other related topics; and includes notes on culture, etiquette, travel, language, and more
Includes bibliographical references (p. 461-464) and index
Keywords: Bulgaria / Guidebooks